2020
DOI: 10.1017/s0007114520002627
|View full text |Cite
|
Sign up to set email alerts
|

Dietary changes in early-stage breast cancer patients from pre-surgery and over the 12 months post-surgery

Abstract: The time after a breast cancer diagnosis is a potential period for making positive dietary changes, but previous results are conflicting. The main aim of the present study was to study breast cancer patients’ dietary changes during the 12 months post-surgery and from 12 months pre-surgery to 12 months post-surgery with repeated administration of a 7-d pre-coded food diary and an FFQ, respectively. Women (n 506), mean age 55·3 years diagnosed with invasive breast cancer (stages I and II), were included. The die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Together it seems that there is a trend toward a higher level for reporting a day as unusual over time, or possibly there are more unusual days with a low energy intake 3 weeks post-surgery than 12 months post-surgery. We have also previously demonstrated among these patients that they did not change their BMI during the same 12-month post-surgery period [ 17 ]. The mean unusual day represents a day with a higher energy intake and a less healthy dietary pattern.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Together it seems that there is a trend toward a higher level for reporting a day as unusual over time, or possibly there are more unusual days with a low energy intake 3 weeks post-surgery than 12 months post-surgery. We have also previously demonstrated among these patients that they did not change their BMI during the same 12-month post-surgery period [ 17 ]. The mean unusual day represents a day with a higher energy intake and a less healthy dietary pattern.…”
Section: Discussionmentioning
confidence: 80%
“…although there were minor differences in the consumption of nutrients/food groups on the normal and unusual days over time. Previously, we have demonstrated that overall the breast cancer patients did mostly not change their diet during the 12-month post-surgery period [ 17 ]. Nevertheless, here we observe a small, statistically significant increase in the intake of energy and sweets, cakes, and snacks on the days characterized as unusual and a tendency toward a lower intake on the normal days over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the findings could be limited by the use of self‐reported data for constructing the score. However, the questionnaires used have been validated for the majority of components included in the score, 8 , 9 , 38 , 39 , 40 , 41 and mostly shown to produce acceptable results. Last, all participants recruited to CRCbiome were FIT positive.…”
Section: Discussionmentioning
confidence: 99%
“…A study of the NutriNet-Sant e cohort (n ¼ 696) found that changes following a diagnosis of cancer included decreased vegetable, dairy, meat, soy, and alcohol consumption which cumulatively resulted in significantly lower total protein intake (À17.4 ± 12.5 g/day; p < 0.0001), compared with prediagnosis [16]. Dietary changes post-diagnosis resulting in decreased protein intake have also been observed in patients with breast cancer [17]. Although some of these changes are beneficial to overall health (e.g., decreased alcohol consumption), a diet containing exclusively (i.e., vegan diet) or predominantly (i.e., vegetarian diet) plant-based foods is concerning due primarily to the importance of animal-based protein for skeletal muscle health.…”
Section: Introductionmentioning
confidence: 99%